Study of Etiology, Diagnosis and Treatment of Attention Deficit Hyperactivity Disorder - Mujtaba Mahfooz (Integrated Journal for Research in Arts and Humanities, 2024)
Attention Deficit Hyperactivity Disorder (ADHD) is a behavioral- developmental disorder that causes impulsive reactions, learning disorders and excessive physical activities and is associated with some abnormal behaviors. Attention deficit disorder is diagnosed more often in children. However, this disorder has also been observed in adults. Hyperactivity disorder begins around the ages of 2 to 4 years and 3 to 7 percent of children in the world suffer from this disorderو and the prevalence of this disorder in boys is 2 to 9 times higher than in girls. The present research is descriptive-analytical which was done in the form of a library. The tools for collecting information in this research are psychology books, research articles and reputable national and international scientific journals. According to the researches, it can be said that the most important symptoms of this disorder are the inability to concentrate, excessive mobility, and impulsive behaviors. Psychosocial, biological and genetic factors play a major role in the occurrence of this disorder. To treat this disorder, drug therapy is used in the first step, and psychotherapy approaches such as cognitive behavioral therapy, play therapy, and coaching are used in the next step. Research findings show that if this disorder is not treated, it can disrupt the important functions of a person's life, such as family function, social function, and educational function.